Folk taxonomy and traditional management of cassava (Manihot esculenta Crantz) diversity in southern and central Benin - Agre, A.P.; Gueye, B.; Adjatin, A.; Dansi, M.; Bathacharjee, R.; Rabbi, Ismail Y.; Gedil, Melaku A (2016)
Cassava (Manihot esculenta Crantz) is an important food security crop for poor rural communities, particularly in Africa. At household level, cassava landraces used for cultivation are mainly selected based on farmers' interests, leading to very particular diversity evolution over generations. The structure, composition and factors influencing cassava diversity at that level is not well monitored and under documented. This study aimed at capturing and analyzing local knowledge on cassava genetic diversity and the key parameters affecting it in Benin, for better and sustainable local cassava genetic resources management. The methodological approach was based on field visits, interview using questionnaire and group discussion with farmers. Data were collected from one hundred and ninety eight (198) respondents and analyzed using descriptive statistics. The majority (82%) of the respondents were male, generally 20 to 80 years old. Positive correlation was found between cassava diversity maintained per household with cultivated area and household size (R2 = 0.162). Farmers used mainly stem and leaves characteristics to identify cassava varieties. Plant materials for next season were mostly selected according to the disease (mainly plant free of viral infection) status, size of the stem and number of nodes. The study revealed existence of a high diversity of cassava at the household level. However, various factors constrained cassava production and threats on cassava diversity were observed. Establishment of community field genebank, introduction of new varieties were some of the on-farm conservation strategies proposed by cassava farmers.